ENGINEERING PORTABLE UNDERWATER LAMP AS AN AUXILIARY GEAR FOR PURSE SEINE - Taufiq; Baskoro, Mulyono Sumitro; Mawardi, Wazir; Riyanto, Mochammad (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2023)
Lights are common supporting tool in purse seine fishing in Indonesia. Currently, lamps on purse seines use mercury and metal halide (MH) which require very high electrical power. Therefore, there is a need for an effective underwater light technology alternative with low electric power. The aim of this research is to design a portable underwater lamp (PUL) which can be controlled remotely to support fishing operations. The design engineering process in creating the PUL includes light and buoy construction, temperature testing, light distribution, waterproofing, and motion testing. The results show that the PUL design enables the tools to be controlled remotely. The average temperature of the lamp on the PUL is 40 ⁰C, this temperature is lower than the MH lamp which reaches 250 ⁰C. The light spreads evenly at an angle of 360⁰ to the horizontal and 180° to the vertical. Meanwhile, the results of the lamp motion test showed that the lamp was watertight and highly stable. Keywords: Light emitting diode, Remote control, Waterproof, Electric Power.